The compatibility of dispute resolution with power distance in the construction industry: a perspective based on the statutory adjudication regime. - Aminuddin, Farrah Azwanee (American Society of Civil Engineers (ASCE), 2023)
Recognizing the importance of cash flow in construction, the Malaysian government has introduced the Construction Industry Payment and Adjudication Act 2012 (CIPAA), which represents a significant development to improve cash flow and payment disputes. Power distance is a national culture dimension that measures the extent to which less powerful members of the country expect and accept that power is unequally distributed. Malaysia scores very high on power distance dimension, which indicates people accept a hierarchical order that needs no further justification. The introduction of yet another form of adversarial dispute resolution like adjudication raises the question of cultural compatibility between dispute resolution and the society's power distance. The purpose of this paper is to assess the compatibility of power distance on dispute resolution through a qualitative study from the perspective of CIPAA. The research draws data from 15 semistructured interviews. Through thematic analysis, data were coded and categorized to support the inquiry. Patterns from the data illustrated that adversarial dispute resolution like adjudication is found to be less desirable to the Malaysian construction industry because it creates social frictions to the hierarchy values embedded within a high power value society. The study presents an analysis of a result that power struggle is a problem to a successful dispute resolution process in a high power distance society. It is hoped that the finding will foster awareness of societal implications among policy makers when implementing dispute resolution mechanisms.